The effectiveness of therapeutic ultrasound on myofascial trigger point syndrome on pain and range of motion: systematic review / Noor Hafifi Noor Hisham - Noor Hisham, Noor Hafifi (2014)
The purpose of this study is to investigate the effectiveness of therapeutic ultrasound (US) on myofascial trigger point syndrome (MTrPS) on pain and range of motion (ROM). The literatures were searched through CENTRAL, MEDLINE, eINARL, PEDro and trial registries databases as well as relevant bibliographies from 1950 to June 2012. Only literatures on human subjects with English languages were included. Two (2) reviewers performed the study selection. The eligibility criteria were MTrPS patient, therapeutic US, randomized controlled trial (ReT), studies that compared with no intervention, sham intervention, or other interventions as well as studies that measure on impairment, activity limitation, participation restrictions and quality of life. Two (2) reviewers performed the data extraction and methodological quality assessment developed by The Cochrane Cystic Fibrosis and Genetic Group and PEDro Rf'T's assessment tool respectively. Six (6) of the included studies have moderate methodological quality and positive effects on pain and ROM. Therapeutic US might have potential benefits on MTrPS on pain and ROM, however, the findings cannot be recommended or refuted. More studies need to be conducted to support these findings